Implikasi Prinsip Non Diskriminasi terhadap Kelompok LGBT ditinjau dari Hukum Positif di Indonesia dan Pernikahan Islam - Sabrina Salsabila; Helma Amalia Putri (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
LGBT in Indonesia has become a global and controversial conversation. LGBT people demand freedom from violence and discrimination as part of the inherent human rights of every individual as stipulated in the Universal Declaration of Human Rights (UDHR) in Article 2, Article 7, and Article 22. Positive law in Indonesia also regulates them in Articles of national laws, such as Article 28J (2) of the 1945 Constitution, Article 69 (1), and 73 of Human Rights Law No. 39/1999. Although there are no laws specifically regulating LGBT people in Indonesia, fair and inclusive regulations can provide legal certainty and benefits for the whole community. However, the implementation of the principle of non-discrimination in LGBT regulations still needs to be strengthened. This research uses descriptive qualitative research methods, including descriptive analysis and interpretation of data collected to draw conclusions about phenomena and pre-existing thoughts.